2018
DOI: 10.1037/hea0000631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a methodological infographic on research participants’ knowledge, transparency, and trust.

Abstract: Promisingly, this transparent, visually powerful methodological infographic improved knowledge and trust. Future trials could embed and experimentally test whether such low-cost online infographics improve not only research literacy, but also trial retention, especially among populations with less initial trust about research. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…13 Details about the 4 core constructs, key strategies, originally implemented procedures, and subsequent adaptations of the MMI approach are provided in Table 1. 1,16 A critical consideration for investigators is to determine which comparison to present when discussing pros/cons. This discussion is likely to be most effective if potential participants are explicitly confronted with the most difficult comparison they will encounter during enrollment, such as whether to participate in a trial with considerable participant burden owing to complex trial assessments or relative attractiveness between trial conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Details about the 4 core constructs, key strategies, originally implemented procedures, and subsequent adaptations of the MMI approach are provided in Table 1. 1,16 A critical consideration for investigators is to determine which comparison to present when discussing pros/cons. This discussion is likely to be most effective if potential participants are explicitly confronted with the most difficult comparison they will encounter during enrollment, such as whether to participate in a trial with considerable participant burden owing to complex trial assessments or relative attractiveness between trial conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One avenue could experimentally test specific MMI strategies rather than test the entire approach. 16,23 For example, in online experiments informed by MMI, individuals who read an easy-to-understand, visually powerful, 1-page infographic letter illustrating the detrimental impact of dropouts on trial conclusions had substantially greater research literacy and participant trust in the research team than individuals reading a control letter. 16 A second avenue could leverage optimization trial designs such as the Multiphase Optimization Strategy framework 24 to identify which core MMI constructs and key strategies-or which combinations of these-best enhance participant engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we want to investigate how patients get information material about trials. Kiernan et al [20] found out that with simple measures such as low-cost online infographics improve trial participation in trust in research. Hence, our focus will also be the Internet-based presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Infographics have been used for knowledge translation (Provvidenza et al, 2019) and to convey economic and political information (Scott et al, 2016). They have also been used in teaching (Makarius, 2017), research dissemination (Murray et al, 2017; Thoma et al, 2018) and to improve research literacy and retention among study participants in an intervention trial (Kiernan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%